Investigating Islamic Religious Education Learning Through Technology-Based Interactive Quizzes: Study of Grade 6 Students' Experiences at SDN Rondokuning - Fajri, Zaenol; Safitri, Oktavia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study looks at how students' motivation, engagement, and comprehension of religious concepts are affected when technology-based interactive tests are used. The study analysed the Islamic Religious Education (PAI) learning experiences of sixth-grade pupils using interactive Wordwall-based tests as a cutting-edge teaching method. The problem of low student engagement and excitement for PAI learning was addressed with this strategy. Methodology: The study, which was carried out at SDN Rondokuning, Probolinggo, used an exploratory qualitative design. Data were gathered through direct classroom observations, in-depth interviews with educators and learners, and recording educational activities and test results. Thematic analysis was employed to find essential trends in the students' experiences. Triangulation procedures were used to guarantee the data's validity and reliability. Main Findings: The findings demonstrated that interactive tests considerably raised student interest, comprehension of religious content, and involvement. Average quiz scores rose by 15%, learner satisfaction improved, and participation rates rose from 60% to 90%. Students also showed improved social interaction, teamwork, and the incorporation of Islamic principles into their everyday lives. Effective school management can reduce technical limitations like erratic internet connectivity. Novelty/Originality of this study: This study is distinctive because it used an exploratory qualitative methodology to examine Islamic Religious Education (PAI) instruction at the elementary school level, accounting for cognitive development and emotional, social, and spiritual factors.